The puzzler's mansion - Berlin, Eric (Berlin, Eric. Puzzling world of Winston Breen., 2013)
Winston Breen and his friends attend a weekend of puzzles and games at a famous musician's mansion. But when someone starts stealing valuable things, Winston must solve the mystery and catch the thief. Includes puzzles for readers to solve throughout the text.